2016 IEEE 16th International Conference on Data Mining (ICDM) 2016
DOI: 10.1109/icdm.2016.0055
|View full text |Cite
|
Sign up to set email alerts
|

Convolutional MKL Based Multimodal Emotion Recognition and Sentiment Analysis

Abstract: Abstract-Technology has enabled anyone with an Internet connection to easily create and share their ideas, opinions and content with millions of other people around the world. Much of the content being posted and consumed online is multimodal. With billions of phones, tablets and PCs shipping today with built-in cameras and a host of new video-equipped wearables like Google Glass on the horizon, the amount of video on the Internet will only continue to increase. It has become increasingly difficult for researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
249
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 488 publications
(271 citation statements)
references
References 31 publications
3
249
0
1
Order By: Relevance
“…In a study using an acted emotion corpus, Busso et al reported an accuracy of 89% in recognizing four classes of emotion, a significant improvement compared to the accuracy of 70.9% with speech-based system and 85% with facial expression based system [37]. This finding is reaffirmed by Poria et al who reported improvement when fusing three modalities into a single emotion recognizer [38]. Another study by Nojavanasghari et al focusing on spontaneous emotions in children also reported the same trend, with best overall performance at 69% [39].…”
Section: Resultssupporting
confidence: 74%
“…In a study using an acted emotion corpus, Busso et al reported an accuracy of 89% in recognizing four classes of emotion, a significant improvement compared to the accuracy of 70.9% with speech-based system and 85% with facial expression based system [37]. This finding is reaffirmed by Poria et al who reported improvement when fusing three modalities into a single emotion recognizer [38]. Another study by Nojavanasghari et al focusing on spontaneous emotions in children also reported the same trend, with best overall performance at 69% [39].…”
Section: Resultssupporting
confidence: 74%
“…Poria et al (Poria et al, 2015(Poria et al, , 2016d) extracted audio, visual and textual features using convolutional neural network (CNN); concatenated those features and employed multiple kernel learning (MKL) for final sentiment classification. (Metallinou et al, 2008) and (Eyben et al, 2010a) fused audio and textual modalities for emotion recognition.…”
Section: Related Workmentioning
confidence: 99%
“…This allows analysts in government, commercial and political domains who need to determine the response of people to different crisis events [5,40,59]. Similarly, online reviews need to be summarized in a manner that allows comparison of opinions, so that a user can clearly see the advantages and weaknesses of each product merely with a single glance, both in unimodal [60] and multimodal [50,9] contexts. Further, we can do in-depth opinion assessment, such as finding reasons or aspects [46] in opinion-bearing texts.…”
Section: Subjectivity Detectionmentioning
confidence: 99%